Sekolah Efektif: Kontribusi Kepemimpinan dan Budaya Sekolah - Muhammad Fadhli (JMiE (Journal of Management in Education), 2018)
Abstrak. Penelitian ini bertujuan untuk mengetahui (1) hubungan Kepemimpinan Kepala sekolah dengan keefektifan sekolah,(2) hubungan budaya sekolah dengan keefektifan sekolah (3) hubungan kepemimpinan kepala sekolah dan budaya sekolah dengan keefektifan sekolah. Hasil penelitian menunjukkan (1) terdapat hubungan yang positif dan signifikan antara kepemimpinan kepala sekolah dengan keefektifan sekolah dengan koefisien korelasi rx1y= 0.497. Sumbangan efektif yang diberikan oleh variabel kepemimpinan kepala sekolah dengan keefektifan sekolah terhadap keefektifan sekolah adalah sebesar 18.77%, (2) terdapat hubungan yang positif dan signifikan antara budaya sekolah dengan keefektifan sekolah dengan koefisien korelasi rx2y= 0.525. Sumbangan efektif yang diberikan oleh variabel budaya sekolah terhadap keefektifan sekolah adalah sebesar 21.96% dan (3) terdapat hubungan yang positif dan signifikan antara kepemimpinan kepala sekolah dan budaya sekolah dengan keefektifan sekolah dengan koefisien korelasi r = 0.638. Kata kunci: Kepemimpinan kepala sekolah, budaya sekolah, sekolah efektif. Abstract. Towards Effective Schools: Leadership and School Culture Contribution. The study aims at determining (1) the correlation between principal leadership and school effectiveness, (2) the correlation between school culture and school effectiveness (3) the correlation between principal leadership and school culture towards school effectiveness. The results of this study revealed that (1) there is a positive and significant correlation between principal peadership and school effectiveness, with the correlation coefficient rX1Y = 0.497. The effective contribution given by the principal leadership variable with school effectiveness towards school effectiveness was 18.77%, (2) there is a positive and significant correlation between school culture and school effectiveness with the correlation coefficient rX2Y = 0.525. The effective contribution given by the school culture variables to the effectiveness of schools is 21.96% and (3) there is a positive and significant correlation between principal leadership and school culture towards school effectiveness with a correlation coefficient R = 0.638.. Keywords: marketing services, education, Islamic elementary school